Beyond mean pharyngeal constrictor dose for beam path toxicity in non-target swallowing muscles: Dose–volume correlates of chronic radiation-associated dysphagia (RAD) after oropharyngeal intensity modulated radiotherapy. Issue 2 (February 2016) - ,; Dale, Timothy; Hutcheson, Katherine; Mohamed, Abdallah S.R.; Lewin, Jan S.; Gunn, G. Brandon; Rao, Arvind U.K.; Kalpathy-Cramer, Jayashree; Frank, Steven J.; Garden, Adam S.; Messer, Jay A.; Warren, Benjamin; et al.
Abstract: Purpose/objective(s): We sought to identify swallowing muscle dose–response thresholds associated with chronic radiation-associated dysphagia (RAD) after IMRT for oropharyngeal cancer. Materials/methods: T1–4 N0–3 M0 oropharyngeal cancer patients who received definitive IMRT and systemic therapy were examined. Chronic RAD was coded as any of the following ⩾12 months post-IMRT: videofluoroscopy/endoscopy detected aspiration or stricture, gastrostomy tube and/or aspiration pneumonia. DICOM-RT plan data were autosegmented using a custom region-of-interest (ROI) library and included inferior, middle and superior constrictors (IPC, MPC, and SPC), medial and lateral pterygoids (MPM, LPM), anterior and posterior digastrics (ADM, PDM), intrinsic tongue muscles (ITM), mylo/geniohyoid complex (MHM), genioglossus (GGM), masseter (MM), buccinator (BM), palatoglossus (PGM), and cricopharyngeus (CPM), with ROI dose–volume histograms (DVHs) calculated. Recursive partitioning analysis (RPA) was used to identify dose–volume effects associated with chronic-RAD, for use in a multivariate (MV) model. Results: Of 300 patients, 34 (11%) had chronic-RAD. RPA showed DVH-derived MHM V69 (i.e. the volume receiving ⩾ 69 Gy), GGM V35, ADM V60, MPC V49, and SPC V70 were associated with chronic-RAD. A model including age in addition to MHM V69 as continuous variables was optimal among tested MV models (AUC 0.835). Conclusion: In addition to SPCs, dose to MHM should be monitored and constrained, especially in older patients (>62-years), when feasible.